Further Evidence of a Left Hemisphere Specialization and Genetic Basis for Tool Use Skill in Chimpanzees (Pan troglodytes): Reproducibility in Two Genetically Isolated Populations of Apes - Hopkins, William D. (J Comp Psychol, 2019)
It has been hypothesized that the evolution of tool use may have served as a preadaptation for the emergence of left hemispheric specialization in motor skill in humans. Here, we tested for intermanual differences in performance on a tool use task in a sample of 199 captive chimpanzees in relation to sex, age and their hand preference. Additionally, we examined heritability in tool use skill for the entire sample, as well as within two genetically isolated populations of captive chimpanzees. This was done to determine the degree of reproducibility in heritability on motor performance. The results revealed a significant effect of hand preference on intermanual differences in performance. Right-handed chimpanzees performed the task more quickly with their right compared to left hand. In contrast, no significant intermanual differences in performance were found in left- and ambiguously-handed apes. Tool use performance was found to be significantly heritable for overall performance, as well as separately for the left and right hands. Further, significant heritability in tool use performance was found in both populations of apes, suggesting these results were reproducible. The results are discussed in the context of evolutionary theories of handedness and hemispheric specialization and the genetic mechanisms that underlie their expression in primates, including humans.